Architecture of the Tuggang Bosar (King Najungal) Palace in South Tapanuli District, North Sumatra - Siti Holizah Harahap; Yusra Dewi Siregar (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
The article discusses the architectural pattern of Raja Najungal's Palace in South Tapanuli Regency. This palace was founded by Raja Tuan Patuan Nagaga Najungal, he was Sultan Haji Baharuddin Harahap, a descendant of Ompu Toga Langit who was the ancestor of the Harahap clan. With a focus on identifying architectural characteristics and analyzing its historical value. The research methods used include field surveys, analysis of historical documentation, as well as studies of traditional architecture and the history of the Sultanate of Raja Najungal. This palace has a unique decoration. Some of the carvings contained in the architectural patterns of king Najungal's palace buildings are on the left and right of the gate there are two elephant statues, the gate ornament is in the form of steps, consisting of five levels and five small domes. The architecture is Angkola and Malay styled, the eight yellow building pillars that support the palace roof are made high, on the roof of the building there are tree classic domes. This research also discusses the implications of the historical and cultural values of the architecture of this palace building in the context of the history of the Sultanate of king Najungal and the cultural heritage that is still relevant today.